2007
DOI: 10.1159/000095200
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Melatonin Rhythms in Teleost Fish

Abstract: Melatonin (N-acetyl-5-methoxytryptamine) is synthesized in the pineal organ and the retina of vertebrates. In some teleost species, ocular melatonin levels can exhibit a circadian periodicity with elevated levels during the dark phase under light-dark (LD) cycles and this periodicity can persist even under constant dark (DD) cycles. However, reversed melatonin profiles and an absence of circadian ocular melatonin rhythms have also been reported. In this study, we investigated the daily rhythms of ocular melato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 72 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…It is generally believed that melatonin is produced by the photoreceptor cells in a circadian manner and that it acts as an autocrine and paracrine modulator of retinal function (Green and Besharse, 2004;Iuvone et al, 2005;Iigo et al, 2007). However, we have recently demonstrated that cells from the INL and GCL also expressed the enzymes of the melatonin synthesizing pathway, the arylalkylamine N-acetyltransferase (AANAT) and hydroxyindole-O-methyltransferase (HIOMT) in trout (Besseau et al, 2006) and seabass (unpublished) retinas.…”
Section: Discussionmentioning
confidence: 97%
“…It is generally believed that melatonin is produced by the photoreceptor cells in a circadian manner and that it acts as an autocrine and paracrine modulator of retinal function (Green and Besharse, 2004;Iuvone et al, 2005;Iigo et al, 2007). However, we have recently demonstrated that cells from the INL and GCL also expressed the enzymes of the melatonin synthesizing pathway, the arylalkylamine N-acetyltransferase (AANAT) and hydroxyindole-O-methyltransferase (HIOMT) in trout (Besseau et al, 2006) and seabass (unpublished) retinas.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, the pineal organ in fish could potentially be involved in mediating the effects of LD cycles on circadian locomotor activities [24,25,[31][32][33][34][35][36][37][38][39]. However, ocular melatonin rhythms in teleost fish, including the Japanese sea catfish, has been reported [40]. Thus, the pathways and organs involved in the entrainment of biological rhythms, and a site of circadian oscillator are unknown for the Japanese sea catfish.…”
Section: Discussionmentioning
confidence: 99%
“…In a number of teleost species, rhythmic melatonin production by both tissues is in phase (low during day and high at night) while in some other vertebrates (including teleosts), melatonin production in retina can be reversed thus being higher during the day than at night (Gern et al, 1978;Yu et al, 1981;Reiter et al, 1983;Serino et al, 1993;Iigo et al, 1997;Besseau et al, 2006;Iigo et al, 2007b). These phase shift patterns of secretion could be linked to differences within the melatonin biosynthesis pathway leading to the production of melatonin and more specifically arylalkylamine N-acetyltransferase (AANAT) which is the enzyme found in all vertebrates involved in the conversion of serotonin into melatonin (Klein et al, 1997).…”
Section: Introductionmentioning
confidence: 99%